Statistical analysis of dental variation in the Oligocene equid Miohippus (Mammalia, Perissodactyla) of Oregon. (20th July 2017) - Famoso, Nicholas A.
Abstract: As many as eight species of the "anchitherine" equid Miohippus have been identified from the John Day Formation of Oregon, but no statistical analysis of variation in these horses has yet been conducted to determine if that level of diversity is warranted. Variation of the anterior-posterior length and transverse width of upper and lower teeth of Turtle Cove Member Miohippus was compared to that of M . equinanus, Mesohippus bairdii, Equus quagga, and Tapirus terrestris using t tests of their coefficients of variation ( V ). None of the t tests are significant, indicating that the variation seen in Turtle Cove Miohippus is not significantly different from any of the populations of other perissodactyls examined in this study. Data also indicate that Mesohippus is present in the Turtle Cove Member. Additionally, hypostyle condition, used to diagnose all species of Miohippus, was found to be related to stage of wear using an ordered logistic regression. Only two species of equid, one Miohippus and one Mesohippus, in the Turtle Cove Member can be identified, therefore only Miohippus annectens, the genotype and first species described from the region, can be recognized as the sole Miohippus species known from the Turtle Cove assemblage. There are insufficient data to determine which species of Mesohippus is present. The dependence of hypostyle condition on crown height in Miohippus implies that wear stage must also be considered in investigations of dental morphology in the "Anchitheriinae."